Entrepreneurial careers: Factors influencing entrepreneurial intentions using a sample of undergraduate exit students - Ndovela, M.; Chinyamurindi, W. T. (South African Journal of Higher Education, 2021)
Entrepreneurship is being encouraged as a possible career path especially within a context of high unemployment that mostly affects the youth. The study sought to empirically investigate the factors influencing entrepreneurial intentions using a sample of undergraduate exit students within a South African higher education (HE) context using a sample of final year students at a university campus in Durban. Researching the factors that influence entrepreneurial intentions can be a useful precursor to interventions that assist students. A sample of 320 respondents were surveyed from a Durban university campus. To determine relationships of the variables, correlation and regression tests were used. The results attest to the importance of the theory of planned behaviour in studies of this nature. Further, relationships existed between personality and participation in entrepreneurial education with entrepreneurial intentions. The study findings have implications for practitioners who may work in a space that encourages entrepreneurship development and education initiatives targeted at students in institutions of higher learning. The findings may serve as a catalyst for developing learning materials and creating opportunities that encourage entrepreneurship development and education.